Marosa di Giorgio and Juana Molina: employing voice as a tool for imagination (Anclajes, 2025)
In 2008, the Argentine singer Juana Molina released the song “Los hongos de Marosa”, establishing a link with poet Marosa di Giorgio by taking up her topics and expressions. This article analyzes how the singer reworks the imaginative work of the poet from Salta starting from the notion of material imagination, and delves into the enunciative forms in which Molina's work of rewriting operates, by forming bodies open to other-than-human ontologies. To do this, we delve deeper into the singing of poetry (music) and poetry as ways that make it possible to diagram imaginations that enable a living and fragmentary materiality. We take up discussions around the material imagination in order to analyze the writing of Marosa di Giorgio in relation to the ideas of new materialisms, particularly on the basis of the Gaia Thesis. Finally, we discuss theories around the voice and how Juana Molina receives the work of Marosa di Giorgio to continue imagining other forms of life.
Keywords: Marosa di Giorgio; Juana Molina; Literary Criticism; Southern Cone; 21st Century